Lex Capitalocenae - Jeremy Santora (Journal of World-Systems Research)
Lex Capitalocenae addresses a lacuna in the Transition Debate by reconstructing the origins of international law in the formation of the capitalist world-ecology in the long sixteenth century (c. 1450–1650). In doing so, this paper bridges a rift in Marxist legal scholarship between the commodity form theorists who emphasize the importance of doctrine and the social property form theorists who stress the determinative role of legal practices. Unacknowledged in this exchange is Wallerstein’s historical-geographic account of the transition and its development by Moore into a political Marxism on a world-scale. Through this perspective, I empirically narrate the centrality of legal transformations surrounding property, territoriality, and Naturalism. The formation of capitalism as a world-ecology, as a way of organizing human and extra-human life, cannot be understood without accounting for the emergence of its legal infrastructure and its dualistic source code—Civilization and Nature—amidst the long sixteenth century. It was only through the failure of the Spanish imperial project that concepts of property, territoriality, and Natural law were revolutionized to create the juridical basis for the capitalist world-ecology and its political structure of nation-states. This geohistorical reconstruction of law, life, and the rise of capitalism allows us to better grasp contemporary debates over planetary law in the climate crisis.